FACTORS ASSOCIATED WITH DIARRHEA MANAGEMENT IN CHILDREN UNDER FIVE YEARS IN INDONESIA - Syahla 'Asilah; Erni Astutik; Rukhsana Khan (Jurnal Berkala Epidemiologi, 2022)
Background: Diarrhea is the highest cause of death for toddlers globally. The proper management of diarrhea can prevent death from diarrhea, and the mother is the key to selecting handlers against diarrhea in the child. Purpose: This study aims to assess factors related to diarrhea management in children under five years in Indonesia. Methods: The type of research is observational analytics with a cross-sectional design. Maternal data analyzed in this study were 819 data obtained from the IDHS in 2017. Multivariable Logistic Regression is used to analyze the data. Results:  Fifty-eight point five percent of all toddlers had poor diarrhea management. It consists of toddlers with a maternal age range of 20-24 years (p=0.04; AOR=2.37, 95%CI=1.03-5.41), and toddlers with a maternal age range of 30-34 years (p=0.03; AOR=2.47, 95%CI=1.07-5.68). Moreover, there are toddlers with a maternal age range of 45-49 years (p=0.03; AOR=13.34, 95%CI=1.25-146.80), toddlers with maternal age older than fathers (p=0.03; AOR=2.04, 95%CI=1.09-3.80), toddlers of mothers with several living children is 1-2 (p=0.02; AOR=2.59, 95%CI=1.19-5.62), and toddlers with a residence in rural areas (p=0.02; AOR=1.52, 95%CI=1.06-2.19) have a higher chance of getting poor diarrhea treatment. Conclusion: The factors of diarrhea management, such as the mother's age, the difference in age between men and women, number of living children, and residence, have a significant link with diarrhea in children under five years.